2020
DOI: 10.1007/s00787-020-01602-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity, somatic comorbidity and substance use in an adolescent psychiatric population at 3-year follow-up

Abstract: Knowledge is scarce on the course of psychiatric disorders in adolescence. We aimed to assess changes in the frequency of psychiatric disorders, somatic disorders, pain, and substance use in a clinical psychiatric cohort from adolescence to young adulthood. This study is part of the Health Survey in Department of Children and Youth, St. Olavs Hospital, Norway. At age 13-18 years, 717 (43.5% of eligible) participated in the first study visit (T 1) in 2009-2011, 549 were reassessed 3 years later with telephone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…It's not easy to know if cannabis and other illegal drugs exist unless someone is in the loop of business which is done in secrecy [31]. These findings were relatively similar to those reported in a cross-sectional study in lake zone Tanzania whereby [18] and other countries such as Sweden [36], Norway [17,32,33], and Nigeria [7]. Similarities in the type of substance (s) commonly used among patients with mental illness between the current study and other studies can be explained by the availability of the particular substances in those countries and the patient's characteristics.…”
Section: Commonly Used Substances Among Patients With Mental Illnesssupporting
confidence: 73%
“…It's not easy to know if cannabis and other illegal drugs exist unless someone is in the loop of business which is done in secrecy [31]. These findings were relatively similar to those reported in a cross-sectional study in lake zone Tanzania whereby [18] and other countries such as Sweden [36], Norway [17,32,33], and Nigeria [7]. Similarities in the type of substance (s) commonly used among patients with mental illness between the current study and other studies can be explained by the availability of the particular substances in those countries and the patient's characteristics.…”
Section: Commonly Used Substances Among Patients With Mental Illnesssupporting
confidence: 73%
“…Many of these adolescents have experienced IPV [ 7 ]. Previous results from the current study has shown that three out of four adolescents still had a psychiatric disorder 3 years after inclusion, and that chronic pain, smoking and trying illicit drugs were associated with persisting psychiatric disorders [ 30 ].…”
Section: Introductionmentioning
confidence: 76%
“…In the general population, the prevalence of multisite pain in both sexes had increased from Young-HUNT3 to HUNT4 but was still lower than that observed for in CAP. Additional descriptive statistics are published elsewhere [2].…”
Section: Sample Characteristics and Chronic Pain Prevalencementioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) typically emerges in childhood with an average global prevalence of 5%, often with difficulties continuing into adulthood [1], frequently showing high concurrent comorbidity with other neurodevelopmental and psychiatric disorders [2]. ADHD diagnosis differs in level of core symptoms (inattentive or hyperactive presentation, or both), impairments, and comorbidities [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation